2012
DOI: 10.1002/ijc.27696
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer and RASSF family—A special emphasis on RASSF1A

Abstract: The RAS‐association domain family, commonly referred to as RASSF, is a family of 10 members (RASSF1‐10) implicated in a variety of key biological processes, including cell cycle regulation, apoptosis and microtubule stability. Furthermore, RASSFs have been implicated in tumorigenesis and several family members are now thought to be tumor suppressors. As opposed to the KRAS oncogene, for which mutational activation is frequent in colorectal cancer (CRC), RASSFs are found to be silenced mainly by aberrant promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 91 publications
1
35
0
Order By: Relevance
“…35 Also in this case, RASSF1A methylation levels varied with studies ranging from 10-20% of CRC subjects up to 40-50%, with some authors observing RASSF1A methylation in early stages of CRC, and others reporting it more frequently methylated in later stages. [35][36][37] Some correlations with tumor stage were also observed in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…35 Also in this case, RASSF1A methylation levels varied with studies ranging from 10-20% of CRC subjects up to 40-50%, with some authors observing RASSF1A methylation in early stages of CRC, and others reporting it more frequently methylated in later stages. [35][36][37] Some correlations with tumor stage were also observed in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Methylation-associated inactivation of RASSF1A, described in many colorectal samples [20], suggests a synergistic effect between the silencing of the tumor suppressor gene RASSF1A and activation of the oncogene KRAS. Thus, RASSF1A methylation represents an alternative mechanism of aberrant RAS signaling [21]. In colon cancer, the interaction between RAS and β-catenin activation was studied [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the tumor-suppressor gene RASSF1A has been extensively investigated and a considerable amount of studies have identified that loss of expression of RASSF1A was shown to participate in the pathogenesis of a variety of human cancers, such as lung cancer and breast cancer, as well as CRC (Chen et al, 2012;Kang et al, 2012). Increasing evidence has shown that loss or aberrant expression of RASSF1A is thought to be significantly correlated with methylation of the CpG-island promoter sequence of RASSF1A, which may alter the function or activity of RASSF1A, thereby playing an important role in promoting the progression and metastasis of CRC (Kimura et al, 2009;Tommasi et al, 2011;Fernandes et al, 2013). Therefore, RASSF1A promoter methylation is generally postulated to be involved in the development and progression of CRC (Sinha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%